'Epidemiology of surgical site infection in a neurosurgery department'. (2nd January 2017) - López Pereira, Patricia; Díaz-Agero Pérez, Cristina; López Fresneña, Nieves; Las Heras Mosteiro, Julio; Palancar Cabrera, Aurelio; Rincón Carlavilla, Ángela Lourdes; Aranaz Andrés, Jesús María
Abstract: Objective: To know the rates of infection of the surgical wound in the Department of Neurosurgery between 2011 and 2014. Methods: An observational, prospective study was conducted of the rates of surgical wound infection among patients admitted for more than 48 h to the Neurosurgery Department of a tertiary-level university hospital between July 2011 and December 2014. Results: The study surveyed a total of 536 surgical procedures performed in 521 patients. The rate of diagnosed surgical site infection (SSI) was 4.85% (26 infections), below the established acceptable threshold of 5%. Of these, 65.38% were organ-space infections, 30.77% deep infections, and 7.69% superficial infections. Infection rates for each type of surgical procedure were 4.35% for spinal fusion, 0.00% for refusion of spine, 2.08% for laminectomy, 5.95% for ventricular shunt, and 5.14% for craniotomy. Antibiotic prophylaxis was evaluated as suitable in 80.22% of surgical procedures. Discussion and conclusions: Infection rates were lower when the surgery was elective, clean, the patient had a lower ASA, and when suitable antimicrobial prophylaxis was administered. The rate of suitable antimicrobial prophylaxis shows that there is room for improvement. In order to minimize the risk of surgical wound infection, all professionals involved in patient care need to know and apply current recommendations, especially those relating to proper hand hygiene and suitable antibiotic prophylaxis.